Structural Performance Testing of Bridges Through Static and Dynamic Loads - Lubab, Lubab; Rohman, Rosyid Kholilur; Rendrarini, Diana (ASTONJADRO, 2026)
This study was conducted to evaluate the structural performance of a bridge whose condition was uncertain due to aging, increased traffic loads, and limited information on its structural details. The objective of the research is to assess the actual condition of the bridge through static and dynamic load testing, compare field responses with theoretical analysis, and determine the operational feasibility of the structure. The methodology includes preliminary data collection, installation of instruments such as LVDTs, strain gauges, accelerometers, and leveling equipment, followed by static load testing using four test trucks representing 70% of the design live load. Dynamic testing was carried out using impulse tests, moving-load tests, and measurement of the Dynamic Amplification Factor (DAF). The results show that the measured deflection is lower than the theoretical deflection with a ratio ≤ 1.0, and deflection recovery exceeds 90%, indicating elastic behavior without permanent deformation. Dynamic testing recorded natural frequencies ranging from 2.9 to 6.8 Hz, while DAF values remained below 1.3, demonstrating that the bridge maintains adequate stiffness and vibration performance within standard limits. No new cracks, structural distress, or signs of capacity reduction were observed during or after testing. Overall, the bridge is concluded to be structurally sound and safe for continued operation without the need for additional load restrictions.